Less Burden, More Transparency, and Higher Quality : Electronic System for Business Safety Inspections in Peru - Barron, Manuel (World Bank, Washington, DC, 2020)
Business safety inspections are commonly cited as one of the most important bureaucratic barriers to doing business around the developing world (World Bank 2019, 2020). In Peru, the business safety inspection system is characterized by low compliance with established norms, misaligned incentives and high transaction costs. These inefficiencies affect micro, small, and medium enterprises (MSMEs) disproportionally, as they do not have the resources or know-how to navigate the inspection procedures. MSMEs constitute 99.5 percent of firms, employ up to 89 percent of the population, and contribute up to 31 percent of gross domestic product (GDP) in the country (Ministry of Production 2017). Thus, the inefficiencies in the inspection system hamper the business environment, adversely affecting shared prosperity and economic growth. The World Bank Group is conducting a rigorous impact evaluation study in collaboration with the Ministry of Housing of Peru.1 Specifically, it will assess how the deployment of an electronic system for inspections, in combination with the improved monitoring of inspector performance and optimized firm auditing, can be used to address key constraints in the inspection system. This work will shed light on whether these mechanisms can reduce the compliance burden on firms by improving regulatory efficiency while also ensuring safety. In addition, it will provide evidence about how such systems could operate when implemented at scale. This note provides an overview of the policy problem that Peru faces, and describes the solutions to be tested. It then focuses on lessons from developing and implementing the electronic system to solve the policy problem, with an emphasis on those lessons related to the constraints and inputs to improving regulatory efficiency and accountability.